EXPANSION OF LEGAL LIABILITY TO HOSPITALS WITH HIGHEST ACCREDITATION - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
The expansion of legal responsibilities in hospitals with the highest accreditation emphasises improved standards of care under stricter regulations. Hospitals with such accreditation must adhere to safety protocols, improve risk management, and ensure effective infection control. A commitment to handle medical complaints or disputes in a transparent and professional manner is part of the expanded legal responsibility, which aims to build patient trust and prevent lawsuits. In addition, strengthening documentation systems, internal audits, and staff training are essential to fulfil national and international standards, support hospitals in facing legal challenges, and ensure the quality and safety of healthcare services provided.